THE RELATIONSHIP BETWEEN ADOLESCENT SANTRI COPING STRATEGIES WITH THE STRESS LEVEL OF MEMORIZING THE QUR’AN AT THE TAHFIDZ AL-QUR’AN AR-ROHMANI BATUJAYA ASSEMBLY IN 2022 - Kurniawan, Agung Triaji; Nurti Y.K. Gea; Hilda Meriyandah (Jurnal Medicare, 2024)
The vulnerability of adolescent students with problems causes stress in the students caused by the obligation of the students to memorize the Qur'an, moreover, the age of the students who are still teenagers and the desire to memorize not all come from themselves, allowing these students to experience stress. Stress can be understood as pressure, a disorder that originates from within (internal) and outside (external) that is unpleasant. There are several factors that influence stress including anxiety, and participation in decision making. Therefore, a strategy is needed to overcome stressors, Each individual has a different coping strategy according to situational and individual. To determine the relationship between the coping strategies of adolescent students and the stress level of memorizing the Qur'an in the Tahfidz Al-Qur'an Ar-rohmani Batujaya Assembly.The research method uses a cross-sectional design. The sampling technique is total sampling, with a total of 50 respondents. The instrument used is a questionnaire. Based on data analysis used using the Chi Square Test with p = 0.00 (p < 0.05). The conclusion is that there is a relationship between the coping strategies of adolescent students and the stress level of memorizing the Qur'an in the Tahfidz Al-Qur'an Ar-rohmani Batujaya Assembly.there is a relationship between the coping strategy of adolescent students and the stress level of memorizing the Qur'an in the Tahfidz Al-Qur'an Ar-rohmani Batujaya Assembly.